Decreased green autofluorescence of lung parenchyma is a biomarker for lung cancer tissues. Issue 8 (14th May 2022) - Zhang, Mingchao; Zhang, Jie; Teng, Haohua; Zhang, Qing; Xiang, Zhenzhen; Chang, Qing; Tao, Yue; Chu, Tianqing; Ying, Weihai
Abstract: It is highly valuable to discover novel biomarkers for differentiating noninvasively the cancerous tissues from the nonneoplastic tissues of lung cancer. In current study, we determined the green autofluorescence (AF) of the pulmonary parenchyma of lung cancer patients, indicating that decreased green AF of pulmonary parenchyma may be the biomarker of this type: First, the green AF intensity of the cancerous tissues was significantly lower than that of the nonneoplastic tissues of the lung cancer patients; second, the green AF intensity of the nonneoplastic tissues of the lung squamous cell carcinoma was significantly lower than that of the lung adenocarcinoma; and third, "decreased green AF intensity" could be used for differentiating the nonneoplastic tissues and the cancerous tissues. Collectively, our study has suggested that decreased green AF of lung parenchyma is a biomarker for differentiating the cancerous tissues from the nonneoplastic tissues of lung cancer. Abstract : It is of significance to discover novel biomarkers for the cancerous tissues of lung cancer. Our study has indicated that decreased green autofluorescence of pulmonary parenchyma may be the biomarker of this type: The green AF intensity of the cancerous tissues was significantly lower than that of the nonneoplastic tissues of the lung cancer patients, which could be used for differentiating the cancerous tissues from the nonneoplastic tissues.